Examine digital transformation in the Malaysian construction industry - Tan, Kai Wen (2023)
The Malaysian construction industry is a vital component of the country’s economy. As technology advances, digital transformation has become a necessity for continued development and competitiveness of the industry. This research examines the digital maturity of the Malaysian construction industry. A questionnaire survey was conducted, comprising both open-ended and closeended questions. The survey included 24 close-ended questionnaires’ statements covering digital tools and software to appraise the availability of digital infrastructure in construction organizations. Another 25 statements were employed to assess the digital maturity of the construction organization. Furthermore, two open-ended questions sought respondents' opinions regarding encountered challenges and the reasons necessitating digital transformation. The data collected from 202 respondents were subjected to reliability analysis, Friedman test, and Kruskal-Wallis H test. The study found that the overall degree of digital maturity for Malaysian construction industry stands at 60%. Software applications were found to be more prevalent in construction organizations, with data dimension exhibiting the highest level of maturity. The study identified three biggest challenges currently hindering the construction industry: high technology cost, resistance to change, and lack of knowledge and skills. The findings alert industry practitioners as a wake-up call, regulators to develop strategies, and academia to conduct future research on specific areas.